2020
DOI: 10.1007/s11307-020-01542-4
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Development of Near-Infrared-Labeled CD38-Targeted Daratumumab for Optical Imaging of CD38 in Multiple Myeloma

Abstract: Purpose: Cluster of differentiation 38 (CD38) is a promising therapeutic target in multiple myeloma (MM) patients and has resulted in the development of several CD38 immunotherapies. Current methods to evaluate CD38 expression in the preclinical setting include ex vivo flow cytometry and immunohistochemistry, which can be cumbersome and do not give whole-body information. In vivo imaging technologies such as positron emission tomography rely on decay of radioisotopes, limiting the number of molecular interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Previous studies demonstrated the feasibility of fluorophore- or radionuclide-labeled daratumumab for in vivo imaging purposes of CD38-expressing myeloma cells ( 19 , 20 , 41 ). However, targeting the same epitope as daratumumab is only effective in daratumumab-naive patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated the feasibility of fluorophore- or radionuclide-labeled daratumumab for in vivo imaging purposes of CD38-expressing myeloma cells ( 19 , 20 , 41 ). However, targeting the same epitope as daratumumab is only effective in daratumumab-naive patients.…”
Section: Discussionmentioning
confidence: 99%
“…Instead of using a conventional monoclonal antibody, we used nanobody JK36 AF680 , recognizing a distinct, non-overlapping epitope of CD38 for demonstrating the feasibility of specific imaging of daratumumab-pretreated CD38-expressing tumors. Key advantages of using nanobodies over conventional antibodies for in vivo diagnostic purposes include greater ease of production ( 42 ) as well as more favorable imaging kinetics: nanobodies allow for excellent tumor-to-background ratios as early as 6 hours post-injection and for same-day in vivo imaging ( 33 , 41 ), owing to the rapid elimination of excess unbound nanobodies by renal filtration. Furthermore, the risk of allergic infusion reactions is reduced when using nanobodies as opposed to conventional antibodies, owing to their low immunogenicity ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our in vivo imaging results showed that both immunoconjugates had high specificity to GFP + tumor lesions in both mouse models. We, and others, have previously demonstrated that IV injection of human myeloma cells results in diffuse tumor growth in variable regions of bone marrow in mice compared to the localized tumor burden observed in MM.1S SQ mice [ 29 , 30 ]. MM is a plasma cell disorder that causes significant skeletal morbidity within the bone marrow niche.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical evaluation of DARA-IRDye800, in which DARA conjugated to the NIR fluorophore IRDye800CW, revealed a significant (~10×) reduction in vivo in fluorescence intensity for the treated group (listed in Table 3). (Cho et al, 2021) 2.3.5 B cell maturation antigen and signaling lymphocyte activation molecule 7 B cell maturation antigen (BCMA) is a member of the tumor necrosis factor receptor superfamily that is found almost exclusively on mature B cells. Its expression level increases significantly in MM cells, and its expression level is positively correlated with MM progression (Shah et al, 2020).…”
Section: Cluster Of Differentiation 138 and 38mentioning
confidence: 99%